Spionidae (Annelida) from Lizard Island, Great Barrier Reef, Australia: the genera Aonides, Dipolydora, Polydorella, Prionospio, Pseudopolydora, Rhynchospio, and Tripolydora - Radashevsky, Vasily I. (Zootaxa, 2015)
Nineteen species in seven genera of spionid polychaetes are described and illustrated based on new material collected from the intertidal and shallow waters around the Lizard Island Group, northern Great Barrier Reef. Only one of these species had been previously reported from the Reef. Six species are described as new to science, and the taxonomy of seven species should be clarified in the future. Prionospio sensu lato is the most diverse group with 11 species identified in the present study. One species is identified in each of the genera Dipolydora, Polydorella, Rhynchospio and Tripolydora, and two species are identified in each of the genera Aonides and Pseudopolydora. The fauna of spionid polychaetes of the Great Barrier Reef seems to be more diverse than previously described and more species are expected to be found in the future. An identification key is provided to 16 genera of Spionidae reported from or likely to be found on the Great Barrier Reef.